DAUN TORBANGUN (COLEUS AMBOINICUS L) MENINGKATKAN KADAR PROLAKTIN DAN PRODUKSI ASI PADA IBU MENYUSUI - Prahesti, Ratna; Sholihah, Nur Rahmawati (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: Breastfeeding at the beginning of a infant's life is essential because the enhancement of human quality starts from the baby. Breast milk contains substances that can protect babies from bacteria and viruses that cause infections. The failure of exclusive breastfeeding is caused by various factors, one of them include nutrition of breastfeeding mothers. Breastfeeding mothers need to pay attention to their nutrition by consuming foods that have a lactagogue effect or increase and accelerate milk production. Consumption of breastfeeding mothers towards Indonesian traditional plants which have lactagogue effect is still lacking. One of the plants that contains lactagogue is Torbangun (Coleus Amboinicus L) leaf which has effect to increase the volume of milk production. Objective: To find out he effect of giving torbangun (Coleus Amboinicus L) leaves on prolactin levels and milk production of breastfeeding mothers. Methods: This experimental study was conducted on 32 breastfeeding mothers which divided equally into 16 mothers as a control group and 16 mothers as a treatment group. This stude aimed to determine the effect of consumption of Torbangun leaf tea for 14 days on prolactin levels and milk production. Results: The results showed that supplementation of Torbangun leaf tea increased prolactin levels (significance 0.014 (p <0.05)) and milk production (significance 0.046 (p <0.05). Conclusion: The results of the analysis showed that torbangun significantly increased prolactin levels and breast milk production. Lactating mothers can consume torbangun as supplementation which can increase prolactin levels and milk production.